A Contribution to the Design of a Piled Embankment - Kim Huat, Bujang; Ali, Faisal (Universiti Putra Malaysia Press, 1993)
The use of timber or concrete piles offers one solution to the problem of stability and settlement posed by construction of road or highway embankments on soft ground. The idea is to transfer most of the applied load on to a grid of piles, and for reasons of economy, the piles should be spaced as widely as possible and capped individually rather than by a continuous slab. However the mechanism of load transfer from ground to the top of the pile cap appears not to be fully understood. Design methods are empirical, based on the results of low stress level model tests on sand, and on field experiences. Using centrifugal and laboratory model tests the influences of parameters such as fill height, pile area ratios and fill properties on the load sharing between the pile and ground are examined and described in the paper.